Respuestas
Respuesta dada por:
1
Necesitas despejar la misma variable de ambas ecuaciones y después igualarlas:
![y=65-9x \\ y= \frac{55-5x}{3} \\ \\ 65-9x= \frac{55-5x}{3} \\ 3(65-9x)=55-5x \\ 195-27x=55-5x \\ 195-55=27x-5x \\ 140=22x \\ x= \frac{140}{22}= \frac{70}{11}\\ \boxed{x= \frac{70}{11} } \\ \\ y=65-9x=65-9( \frac{70}{11})= \frac{65(11)-630}{11}= \frac{715-630}{11} \\ \boxed{y= \frac{85}{11} } y=65-9x \\ y= \frac{55-5x}{3} \\ \\ 65-9x= \frac{55-5x}{3} \\ 3(65-9x)=55-5x \\ 195-27x=55-5x \\ 195-55=27x-5x \\ 140=22x \\ x= \frac{140}{22}= \frac{70}{11}\\ \boxed{x= \frac{70}{11} } \\ \\ y=65-9x=65-9( \frac{70}{11})= \frac{65(11)-630}{11}= \frac{715-630}{11} \\ \boxed{y= \frac{85}{11} }](https://tex.z-dn.net/?f=y%3D65-9x+%5C%5C+y%3D+%5Cfrac%7B55-5x%7D%7B3%7D++%5C%5C++%5C%5C+65-9x%3D+%5Cfrac%7B55-5x%7D%7B3%7D+++%5C%5C+3%2865-9x%29%3D55-5x+%5C%5C+195-27x%3D55-5x+%5C%5C+195-55%3D27x-5x+%5C%5C+140%3D22x+%5C%5C+x%3D+%5Cfrac%7B140%7D%7B22%7D%3D+%5Cfrac%7B70%7D%7B11%7D%5C%5C+%5Cboxed%7Bx%3D+%5Cfrac%7B70%7D%7B11%7D+%7D+++%5C%5C++%5C%5C+y%3D65-9x%3D65-9%28+%5Cfrac%7B70%7D%7B11%7D%29%3D+%5Cfrac%7B65%2811%29-630%7D%7B11%7D%3D+%5Cfrac%7B715-630%7D%7B11%7D+%5C%5C+%5Cboxed%7By%3D+%5Cfrac%7B85%7D%7B11%7D+%7D+++)
Saludos!
Saludos!
Narik:
Muchisimas gracias
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años